Business Higher Education “In Action” - Cătălina RADU (Revista de Management Comparat International)
This paper aims to highlight the link between competitive business higher education and action learning as an appropriate method for improving the educational process. A really competitive university should focus on both information and capabilities and should permanently adapt to its students and to demands in the work market. Although many ideas are very well understood by simply reading a text or seeing a documentary, every process is really “felt” only when “doing things”. My paper aims to present the general benefits of action learning, by having as a case study a course of Operations Management. I use as a sample my students from the Faculty of Management (second year of study), in the Bucharest Academy of Economic Studies, Romania. Students have to meet both the perspective of traditional learning and action learning. Students have participated in many projects looking as simple games (i.e. they have to organize themselves in teams in order to produce snowmen, hats, pancakes, etc). Debriefing is very important and leads to a series of conclusions for each student that he/she keeps in mind for a long period of time from then on. The main methods used for this paper are observation and a questionnaire in which my students gave a valuable feedback. Results confirm the hypothesis that action learning leads to deeper knowledge of the processes.